Systematization of perioperative nursing care in the surgical center: a report of experience - A. G. Sauer; D. Pasquetti; H. S. Kwiatkowiski; L. J. Pinheiro; D. C. M. Aguiar; G. A. S. Moser; M. C. Hanauer (Scientific Electronic Archives, 2021)
Objective: To report the experience that academics had when performing SAEP in the intraoperative period. Method: This is an experience report that undergraduate Nursing students had when performing the Systematization of Perioperative Nursing Care (SAEP) in a hospital in the western region of Santa Catarina. Results: The Surgical Center is characterized as a differentiated environment, with particular dynamics that require tools to provide quality perioperative care, planned and humanized. For this, SAEP presents itself to assist in the development of effective care, covering all the needs of the patient. Although the implementation of SAEP is essential, in the hospital of the experiences its implementation has not yet occurred, in addition there was a deficit in creating the bond between professionals and patients, essential for the development of humanized care. Conclusion: With the implementation of SAEP, it was realized in practice the importance of its use, as it enables the prevention of complications, comprehensive care, human and recognized.